2020
DOI: 10.15294/jpii.v9i2.23193
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Undergraduate Students’ Misconceptions in Understanding Acid Base Materials

Abstract: Students’ misconceptions have become phenomenon in teaching and learning, especially in chemistry which is considered as difficult subject. The objective of this study is to identify undergraduate student’s misconception profiles related to acid-base concepts in inorganic chemistry. This test was conducted with 15 item three tier multiple choices test. Data were identified descriptively and qualitatively. This test instruments are judged as valid with CVR score of 0,99 and mean of 1,73. Meanwhile, the reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(48 reference statements)
0
5
0
1
Order By: Relevance
“…That is, teachers' misconceptions are not influenced by the usage of everyday language and religion to explain organic chemistry. Indeed, conceptual misunderstanding is becoming one of the common issues in teaching and learning chemistry (Mubarak & Yahdi, 2020), and teachers in this study have misunderstandings in another known difficult concept (Burrows & Mooring, 2015) like organic chemistry. Teachers' conceptual misunderstanding is an indication that they are misapplying basic principles (NRC, 1997) such as the number of bonds formed by each carbon atom in a chain, hybridization of the carbon atom, IUPAC nomenclature, structural formula, and chemical reactions.…”
Section: Discussionmentioning
confidence: 87%
“…That is, teachers' misconceptions are not influenced by the usage of everyday language and religion to explain organic chemistry. Indeed, conceptual misunderstanding is becoming one of the common issues in teaching and learning chemistry (Mubarak & Yahdi, 2020), and teachers in this study have misunderstandings in another known difficult concept (Burrows & Mooring, 2015) like organic chemistry. Teachers' conceptual misunderstanding is an indication that they are misapplying basic principles (NRC, 1997) such as the number of bonds formed by each carbon atom in a chain, hybridization of the carbon atom, IUPAC nomenclature, structural formula, and chemical reactions.…”
Section: Discussionmentioning
confidence: 87%
“…Namun demikian hasil tes twotier tidak cukup menggambarkan kesalahpahaman tentang kurangnya pengetahuan (Anam et al, 2019). Sehingga instrumen diagnostik tes three-tier dianggap lebih valid dan dapat diandalkan dalam mendiagnosis miskonsepsi peserta didik daripada tes two-tier (Mubarak & Yahdi, 2020;Prodjosantoso et al, 2019). Akan tetapi instrumen diagnostik tes four-tier selalu dianggap lebih efektif dan akurat daripada tes three-tier, dan lebih dapat digunakan untuk melihat seberapa kuat peserta didik dalam memahami konsep (Akmali, 2018;Habiddin & Page, 2019).…”
Section: Intrumen Diagnostik Yang Digunakan Dalam Mengidentifikasi Mi...unclassified
“…Students had difficulty understanding the Brownsted-Lowry acid-base concept because they only recognized the Arrhenius acid-base concept. Another study revealed that some students had misconceptions about all concepts (Mubarak & Yahdi, 2020). Therefore, most students had difficulty answering questions about acid-base theory (Fajrin et al, 2020).…”
Section: Description: R = Researcher S = Studentmentioning
confidence: 99%